Analysis of Eco-Efficiency and ESG Disclosure on Financial Performance of LQ45 Companies Listed on the Indonesia Stock Exchange in 2021-2024 - Aliyah Ardiwati Puspita; I Imronudin (Universitas Muhammadiyah Surakarta, 2025)
This study aims to examine the effect of eco-efficiency and ESG disclosure on the financial performance of LQ45 companies listed on the Indonesia Stock Exchange from 2021 to 2024. A quantitative research method was applied using secondary data obtained from annual reports and sustainability reports, with 84 firm-year observations selected through purposive sampling. The analysis was conducted using descriptive statistics and classical assumption tests. The findings indicate that variations in eco-efficiency and ESG disclosure provide meaningful insights into financial performance trends among highly liquid firms. This study offers originality by integrating both sustainability indicators to assess their combined influence on financial performance during the post-pandemic period, contributing to the limited empirical evidence in the Indonesian capital market.